1989
DOI: 10.1021/j100348a034
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of cyclopentadienyliron dicarbonyl dimer and ferrocene in zeolite Y cavities: anchoring organometallic fragments into microporous solids

Abstract: The intracavity chemistry of [CpFe(C0),I2 (1) and ferrocene in different acid forms of zeolite Y has been studied with EXAFS, in situ FTIR, and TPD-MS spectroscopies. Depending on the stoichiometry of zeolite protons vs the amount of starting complex 1, the complex is either oxidatively cleaved into CpFe(CO)3f ( 2 ) and CpFe' coordinated to the zeolite, or protonated to form dimeric [CpFe(C0)2]2H' (3). It is shown that the stability of all complexes is influenced by the intracavity concentration of the zeolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In the analysis of the complexes 1, 4 and 5 the shell was determined at about 1.99-2.07Å corresponding to Fe-C backscatterers arising from the ferrocenyl unit. This value is in good agreement with the reported value [40]. The EXAFS results indicate the attachment of ten carbon atoms of both the cyclopentadienyl ligand to Fe centre.…”
Section: Fe K-edge Investigationsupporting
confidence: 92%
“…In the analysis of the complexes 1, 4 and 5 the shell was determined at about 1.99-2.07Å corresponding to Fe-C backscatterers arising from the ferrocenyl unit. This value is in good agreement with the reported value [40]. The EXAFS results indicate the attachment of ten carbon atoms of both the cyclopentadienyl ligand to Fe centre.…”
Section: Fe K-edge Investigationsupporting
confidence: 92%
“…The analogous surface complexes (SiO) 3 Ti(η 5 ‐C 5 H 5 ) and η 5 ‐CpFe(OZ) 2–3 (Z = Si, or Al) have been reported in the literature by grafting Cp 2 TiCl 2 to MCM‐41 and anchoring [CpFe(CO) 2 ] 2 to HY, respectively at 373–473 K 19b. 44 The calculated structures of this (SiO) 3 Ti(η 5 ‐C 5 H 5 ) intermediate were not, however, in agreement with the experimental EXAFS structure, and force field calculations suggested that the cyclopentadienyl ring is not exactly η 5 ‐bonded to Ti due to steric interactions of the ring with nearby silanols 45.…”
Section: Discussionmentioning
confidence: 58%
“…Reactions of [CpFe(CO)2]2 [23], COTFe(CO)3 [24], CpFe(CO)2CH3 and ferrocene in different acid forms of zeolite Y are described in the following. …”
Section: Inclusion Phenomena and Molecular Recognitionmentioning
confidence: 99%